Design of a 4-bit phase shifter using PIN diodes and high-pass/low-pass topology at 2.45 GHz - Qureshi, Muhammad Tayyab (My University, 2012)
Phase shifters are used phased array antennas for beam steering applications. In this thesis work, a 4-bit digital phase shifter was designed using NXP PIN diode switches and high-pass/low-pass Π filter topology at 2.45 GHz. The phase shifter was designed using momentum simulation on Agilent ADS from Murata and NXP design kits. The Single Pole Double Throw (SPDT) switch was realized using NXP BAP51-04W dual PIN diodes. Resonant inductors and T-attenuators were used, to improve the isolation and return loss of the phase shifter. Digital control circuitry was also implemented to control the different phase states. A Monte Carlo statistical analysis was performed for sensitivity analysis used in test of repeatability. A 4-layer PCB layout was manufactured on FR4 substrate. The 4-bit phase shifters with-attenuators and without-attenuators were measured and characterized using R&S SVA 24 network analyzer. The phase shifter with-attenuators showed RMS phase error less than 3.8°, insertion loss better than 24.5 dB and return loss above 22 dB. The phase shifter without-attenuators showed RMS phase error less than 4°, insertion loss better than 7.9 dB and return loss above 13 dB.
Keywords: Elektroteknik och elektronik; Grundläggande vetenskaper; Signalbehandling; Electrical Engineering, Electronic Engineering, Information Engineering; Basic Sciences; Signal Processing